Using geospatial information to connect ecosystem services and human well-being in Kenya - Nackoney, J.; Henninger, N.; Said, Mohammed Yahya; Okwi, P.O.; Ndeng'e, G.; Landsberg, F.; Kristjanson, Patricia M.; Reid, Robin S.; Tunstall, D.; Mock, G. (SAGE Publications, 2007)
The application of geospatial information in the analysis of ecosystem services would help decision makers to develop programs for poverty reduction in Kenya that would improve the targeting of social expenditures and ecosystem interventions so that they reach areas of greatest need.